Clinical Utility of Intravascular Ultrasound (IVUS) in Carotid Artery Interventions: A Systematic Review and Meta-analysis. (October 2022) - Mishra, B.; Pandit, A. K.; Miyachi, S.; Ohshima, T.; Kawaguchi, R.; Vishnu, V. Y.; Misra, S.; Srivastava, M. V. P.; Srivastava, A. K.; Kale, S. S.; Phalak, M.
Background: Carotid plaque morphology plays an important role in determining outcome of carotid artery stenting (CAS). Intravascular ultrasound (IVUS) and its extension VH (Virtual Histology)-IVUS evaluate plaque characteristics in real time and guide decision making during stenting. To date, there is no consensus about indications of IVUS and its validated methods. This systematic review and meta-analysis aims to evaluate the clinical utility of IVUS in carotid artery interventions (CAS) and develop a future consensus for research and practice parameters. Methods: A systematic review and meta-analysis was performed of the English literature articles published till February 2021. Studies reporting on IVUS parameters and findings and also its performance compared with other imaging modalities were included in review. Pooled prevalence with 95% confidence intervals (CI) was calculated. The statistical analysis was conducted in R version 3.6.2. Results: A total of 2015 patients from 29 studies were included. Proportional meta-analysis was performed on 1566 patients from 11 studies. In 9 studies, stroke/transient ischemic attack (TIA) had a pooled prevalence of 4% (95% CI 3%–5%) while asymptomatic stroke had a pooled prevalence of 46% (95% CI 31%–62%) in 4 studies following IVUS. Two studies reported that IVUS detected more plaque protrusion compared with angiography (n=33/396 vs 11/396). IVUS led to stent type or size change in 8 of 48 cases which were missed on angiography in 3 other studies. Concordance between VH-IVUS and true histology was good at 80% to 85% reported in 2 studies. Conclusions: This systematic review and meta-analysis showed, though IVUS fared better to computed tomography (CT)/magnetic resonance (MR) angiography for better stent selection during CAS, with low to moderate risk of bias in the studies included. However, large scale, preferably randomized controlled studies are needed to predict its role in determining clinical outcome.